Case of generalized morphea complicated with systemic sclerosis - Soichiro Sawamura; Katsunari Makino; Hitomi Nakashima; Takamitsu Makino; Satoshi Fukushima (PAGEPress Publications, 2021)
Dear Editor, Localized scleroderma (LSc; morphea) is a rare fibrosing disease of the skin and underlying tissues, which is different from systemic sclerosis (SSc). 1 LSc is classified based on clinical presentations: circumscribed, linear, generalized, pansclerotic, and mixed morphea. 1 Generalized morphea (GM) , which is characterized by widespread skin lesions with multiple indurated plaques or hyperpigmentation, is a relatively rare subtype occurring in 7-9% of patients with LSc. 1 Previous studies have shown that SSc can be complicated by GM, separately from GM-like SSc. Here, we present a rare case of coexistence of LSc and SSc in which LSc skin lesions appeared before SSc became apparent [...].